Changing play : play, media and commercial culture from the 1950s to the present day - Marsh, Jackie; Bishop, Julia C., 1960- (Open University Press, 2013)
The aim of this book is to offer an informed account of changes in the nature of the relationship between play, media and commercial culture in England through an analysis of play in the 1950s/60s and the present day.